Infrared spectroscopy of hydrated polycyclic aromatic hydrocarbon cations: naphthalene+–water. Issue 48 (1st December 2017) - Chatterjee, Kuntal; Dopfer, Otto
Abstract : The combination of infrared spectroscopy and quantum chemical calculations unravels the salient properties of the bifurcated CH⋯O ionic hydrogen bond typical for the PAH + –H2 O interaction. Abstract : Polycyclic aromatic hydrocarbons (PAHs) are suggested to occur in interstellar media and ice grains. It is important to characterize hydrated PAHs and their cations to explore their stability in interstellar and biological media. Herein, the infrared photodissociation (IRPD) spectrum of the naphthalene + –H2 O radical cation (Np + –H2 O) recorded in the O–H and C–H stretch range is analysed by dispersion-corrected density functional theory calculations at the B3LYP-D3/aug-cc-pVTZ level to determine its structure and intermolecular bonding. Monohydration of Np + in its 2 Au ground electronic state leads to the formation of a bifurcated CH⋯O ionic hydrogen bond (H-bond), in which the lone pairs of H2 O bind to two adjacent CH proton donors of the two aromatic rings. The frequency-dependent branching ratios observed for IRPD of cold Np + –H2 O–Ar clusters allows the estimation of the dissociation energy of Np + –H2 O as D 0 ∼ 2800 ± 300 cm −1 . The monohydration motif of Np + differs qualitatively from that of the benzene cation in both structure and binding energy, indicating the strong influence of the multiple aromatic rings on the hydration of PAH + cations. This difference is rationalized by natural bond orbital analysis of the ionic H-bond motif. Comparison with neutral Np–H2 O reveals the large change in structure and bond strength of the hydrated PAHs upon ionization. While neutral Np–H2 O is stabilized by weak π H-bonds (OH⋯π, π-stacking), strong cation–dipole forces favour a planar bifurcated CH⋯O ionic H-bond in Np + –H2 O.